Teachers' Competence and the Effectiveness of Kindergarten Education Programs: Intervention Strategies in Northern Tabuk District 1, Kalinga - Delin, Brenda; Sabado, Adriano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the competence of Kindergarten teachers, the effectiveness of Kindergarten Education programs, and the intervention strategies employed in public elementary schools in Northern Tabuk District 1, Kalinga. It described the teachers' profile, the implementation of the general objectives of Kindergarten Education, the development of the seven learning domains, the effectiveness of selected teaching factors, the hindrances encountered in instruction, and the interventions used to address these concerns. The study employed a descriptive research design. Twenty Kindergarten teachers served as respondents and answered a structured questionnaire. Data were analyzed using frequency counts, percentages, and weighted means. Findings revealed that the respondents were qualified, experienced, and active in professional development activities. The general objectives of Kindergarten Education were implemented, while the seven domains were developed, with values development and physical health and motor development receiving the highest ratings. Teacher competence, learning materials, classroom environment, parent factor, pupil factor, and instructional supervision were rated effective to very effective. Hindrances were generally least serious to slightly serious, indicating that these concerns did not greatly disrupt instructional delivery. Teachers often applied interventions such as involving parents, using outdoor activities, introducing classroom innovations, and monitoring pupil achievement. The study concludes that Kindergarten Education in Northern Tabuk District 1 is effectively delivered through competent teachers, supportive learning conditions, parental participation, and responsive intervention strategies that help prepare young learners for formal schooling.
Keywords: Early Childhood Education, Intervention Strategies, Kindergarten Education, Program Effectiveness, Teacher Competence